Study on Risk-Informed In-Service Inspection for BWR Piping - KORIYAMA, Tamio; LI, Yinsheng; HAMAGUCHI, Yoshikane; YAMASHITA, Masahiro; HIRANO, Mitsumasa (Journal of nuclear science and technology, 2009)
Risk-informed in-service inspection for piping was studied for a BWR plant. Piping segment rupture probabilities were determined by Bayesian transform from piping failure events in the database of the OECD-NEA Piping Failure Data Exchange project. Based on the methodology of the Westinghouse Owners Group, core damage frequency induced by each segment rupture was determined by the use of a surrogate component in the PSA model. Nondestructive examinations were added to leak examinations for segments of the resultant high risk significance. The changes from current examinations gave around 29% reduction of segments subject to both leak and nondestructive examinations within the total segments. Deterministic insights and engineering judgments on top of risk significance should be applied to obtain the final decision of inspection methods. An extent-of-examination was studied by the adoption of the Perdue-Abramson model in the Westinghouse Owners Group methodology. The necessary leak frequency of a crack in a segment was calculated by the probabilistic fracture mechanics code PRAISE. Two segments of high risk significance showed lower or slightly higher extents-of-examination, respectively, than the current extent-of-examination. To contribute to the enhancement of the scientific rationality of piping inspections, technical knowledge was accumulated.